Rancang Bangun Sistem Pendaftaran Pasien Di Rumah Sakit Universitas Riau Berbasis Android Dan Website - Pinarian Elni Endra Saneni; Ery Safrianti; Linna Oktaviana Sari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Since the inauguration of Regulation the Republic of Indonesia's Minister of Health No. 82 in 2013 concerning Hospital Management Information Systems obligates UNRI Hospital has a system that handles patient registration in the form of an information system. However, since its inauguration in 2013, UNRI hospital has used the Hospital Management Information System (SIMRS) which has been implemented since 2017. UNRI hospital still use conventional methods for patient registration and consultation. Prospective patients must fill in forms and submit equipment documents such as a photocopy of UNRI civitas identity card (for UNRI civitas) and Identity Card (KTP) and to register as a patient before consulting. This research uses Waterfall method in addition to being easily understood this method also has sequential stages so that there are no overlapping stages.. While the system design uses Context Diagrams, Data Flow Diagrams, and Use Case Diagrams. The database used is MySQL with notification feature from Firebase. There are two applications built, namely Website and Android. Website outputs are tested using the Black-Box and Android applications are tested using User Acceptance Likert Scale. Results of the Black-Box test are UNRI Hospital patient registration Websites with criteria such as display menu on the main page, print button on the patient registration page, add button on the notification page, etc. Results of User Acceptance testing on Android bassed on 33 questioner from 30 respondents has produced 87,12% Likert scale results. It can be concluded that android application for UNRI Hospital patient registration that has been made is very satisfied Keywords: Android, MySQL, Firebase Could Massaging, Rumah Sakit Universitas Riau